The life and times of the thunderbolt kid - Bryson, Bill. (London : Black Swan, 2007)
The author describes his childhood growing up in Iowa during the 1950s, recalling country fairs, playing hockey, paper routes, church suppers, and other nostalgic memories.
The author describes his childhood growing up in Iowa during the 1950s, recalling country fairs, playing hockey, paper routes, church suppers, and other nostalgic memories.
Adult.
Adult
Keywords: Bryson, Bill; Bryson, Bill; Travel writers -- United States -- Biography; Travel writers -- Biography